Pretreatment Level of Red Cell Distribution Width as a Prognostic Indicator for Survival in a Large Cohort Study of Male Laryngeal Squamous Carcinoma - Hsueh, Chi-Yao; Lau, Hui-Ching; Li, Shengjie; Tao, Lei; Zhang, Ming; Gong, Hongli; Zhou, Liang (Frontiers in Oncology, 2019)
Objective: High levels of red cell distribution width (RDW) may be associated with adverse outcomes in patients with cancer. The purpose of the present study was to investigate the prognostic impact of pretreatment RDW levels on overall survival (OS), cancer-specific survival (CSS), and disease-free survival (DFS) in a large cohort of male laryngeal squamous cell cancer (LSCC) patients. Methods: A total of 809 LSCC patients who were treated between 2007 and 2011 at the Eye & ENT Hospital of Fudan University were enrolled and evaluated retrospectively. OS, CSS, and DFS were analyzed using the Kaplan–Meier method. To evaluate the prognostic significance of RDW levels, univariate and multivariate Cox analyses were applied. Results: Higher pretreatment RDW levels were significantly associated with high death events, red blood cell count, hemoglobin, radiotherapy, operation therapy, and advanced tumor stage (p < 0.05). From the univariate analysis, we observed that the higher (13.2% - 13.5%) and the highest (> 13.5%) quartiles of RDW level were consistent factors for poor OS, CSS, and DFS in LSCC patients. In the multivariate analysis, after adjusting for confounding factors, the higher and highest quartiles of RDW levels were identified as independent prognostic factors in male LSCC patients. Conclusion: Higher pretreatment RDW levels were demonstrated to be associated with poor clinical outcome in male LSCC patients and might be novel markers for patient stratification in LSCC management.